“I аm an Elephant”: The Use of Metaphor in Contemporary Russian Comics - Ruslan T. Saduov (Studia Litterarum)
This article is a study of contemporary Russian comics as an increasingly popular juvenile genre. The genre is becoming integral part of our literary culture despite certain difficulties it faced at the beginning of its history in Russia. The relevance of this essay is due to the lack of sufficient research of Russian comics. It discusses the comics entitled I am an Elephant that tells the story of a young man in a wheelchair. The metaphor of the elephant forms the basis of the plot and mediates between the character and the reader engaging the latter in the character’s world. The character’s mind unable to adapt himself to the new reality, detaches itself from the body. Throughout the narrative, the reader observes how Anton who is now associating himself with the elephant is trying to reconcile himself with his own body represented as a motionless doll. Yet pain and eventual acceptance of his fate bring the character back to reality. The effective metaphor helps better understand the inner world of the disabled person. The main objective of the essay is to trace the role of the metaphor as the means of representing the character. The comics may be considered socially oriented in that it addresses the problem of relationship between persons with disabilities and society including police and state authorities. In this respect, this comics is socially relevant.